Earnings Management Impact on Financial Performance: Accounting Information System Effectiveness as Moderation - Nur Ariskawati; Silvya Eka Marenza; Sugiyarti Fatma Laela (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This research examines the impact of earnings management on financial performance, with a focus on the moderating role of the effectiveness of Accounting Information Systems (AIS). The research sample consisted of 16 Islamic commercial banks registered with the Financial Services Authority during the 2019-2022 period. Return on Equity (ROE) is used as an indicator of financial performance, while earnings management practices are measured through Discretionary Loan Loss Provisions (DLLP). The effectiveness of AIS is assessed through the timely publication of financial reports and restated reports. This research finds, through panel data regression analysis, that earnings management and an effective AIS increase the financial performance of Islamic banks. Furthermore, AIS effectiveness moderates the positive impact of earnings management on financial performance. The moderation effect shows that a well-functioning AIS can strengthen the impact of efficient earnings management on financial performance. The implications of this research highlight the importance of transparency, and efficient earnings management through an effective AIS. As a result, an investment in AIS is crucial for Islamic banks.